Effect of neoadjuvant chemotherapy on the expression of hormone receptors and Ki-67 in patients with locally advanced breast cancer - Aanchal Gupta; Renuka Verma; Nisha Marwah; Sanjeev Parshad; Priyanka Verma; Sunita Singh (Asian Journal of Medical Sciences, 2024)
Background: Neoadjuvant chemotherapy (NACT) affects the tumor protein marker’s expression and status. Changes in the expression of biomarkers during NACT may influence the clinical decision of adjuvant molecular and hormonal therapy. Hence, re-evaluation of receptor status has to be done after NACT to give a specific adjuvant therapy for patient benefit. Aims and Objectives: The aim of this study was to study the status of hormone receptors (HRs) – estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor (Her-2/Neu), and Ki-67 in patients with locally advanced breast cancer (LABC) in both core needle biopsies and post-mastectomy specimens after administering neoadjuvant chemotherapy. Materials and Methods: The present study was conducted in the Department of Pathology in collaboration with the Department of Surgery, Pt B D Sharma PGIMS, Rohtak, for a period of 1 year. The study comprised 52 patients with LABC who received neoadjuvant chemotherapy and 20 control cases who did not receive neoadjuvant chemotherapy. Each case comprised two specimens: Trucut biopsy and a mastectomy specimen. Results: ER changed from positive to negative in 15.4% of the cases and from negative to positive in 1.9% of the cases. The overall change in ER was statistically significant (P=0.020). For PR, 9.6% of the cases changed from positive to negative while none of the cases showed change from negative to positive. The overall change in PR was statistically significant (P=0.025). For HER2/Neu, 19.2% of the cases changed from positive to negative, and 11.5% of the cases changed from negative to positive. The overall change in HER2/Neu was not statistically significant (P=0.317). For Ki-67, 30% of patients changed from positive to negative while 11.5% of patients changed from negative to positive. The overall change in Ki-67 was statistically significant (P=0.024). Conclusion: There was discordance in the HR status and proliferation marker after NACT in patients with breast cancer. The administration of NACT might be the main reason for the change in receptor status thus understanding the chemotherapy-induced biological conversion in the tumor cell behavior is strategically important in planning adjuvant endocrine therapy and for disease follow-up.